RESPON PETANI TERHADAP EFEKTIVITAS KERJA DI LAHAN IRIGASI TEKNIS (STUDI KASUS DESA CARAWALI KECAMATAN WATANG PULU KABUPATEN SIDENRENG RAPPANG) - Muhammad Ikhsan Tahir; Nurhapsa Nurhapsa; Syamsi Mu’min; Suherman Suherman (JAS (Jurnal Agri Sains), 2018)
This study aims to determine the extent of farmers' response to work effectiveness in managing rice farming in technical irrigated land. This research was carried out in the village of Carawali, Watang Pulu Sub-District, Sidenreng Rappang District. The population in this study were paddy farmers in the village of Carawali, Watang Pulu Subdistrict, 311 people in Sidenreng Rappang District. Sampling is done by incidental sampling technique. The types and sources of data used are primary data and secondary data. Data are described with variables in the study consisting of adaptability, work performance, job satisfaction and farmer's work effectiveness with the average value of each respondent's answer. Farmer's response to work effectiveness has an average value of 3.68. The variable adaptability (X1) obtained an average value of respondents' responses of 3.47. For variebal work performance (X2) obtained an average value of 3.62, while the average response of farmers to the variable job satisfaction (X3) obtained a value of 3.51. The ability to self-adjust coefficient (X1) is -0.278, Work Performance (X2) is 1.148, and farmer's job satisfaction (X3) is 0.072. The ability to adapt, work performance, and job satisfaction in Carawali Village, Watang Pulu Subdistrict, Sidenreng Rappang District is in a good category. Adapting ability is negative and signifies a relationship that is opposed to the effectiveness of the farmer's work. Work performance and farmer's job satisfaction are positive and indicate a unidirectional relationship to the work effectiveness of farmers. The variables in the study gave a correlation of 78.3%, this means there are still 21.7% of other variables that affect the effectiveness of farmer performance. Further research is needed on other variables that affect the performance of rice farmers in technical irrigated land. Keywords: adaptability, job satisfaction, Work Effectiveness, work performance.